Ancient Culinary Science (Soopa Shastra): It’s Usefulness in Today’s Era in Health Point of View (AYUSHDHARA, 2022)
The role of Ahara is very important in human life. It is called sustenance of life which Acharyas refer as Traya upsthambha that implies support of life. Acharya Charaka has mentioned the three supports of life, as food (Ahara) intake, sleep (Nidra) and observance of celibacy (Brahmacharya). In these three components Ahara is very important because it is Panchabhautika, human body is Panchabhautik and whatever diseases are caused also Panchabhautika and therefore our body would be formed as what we consumed food articles. Gradually human beings started taking cooked food items from raw food materials due to advancement of civilization. Later on because of evolution of food item people used to consume varieties of cooked food items with enhanced nutrition and taste. Therefore Ahara paka process is very important for healthy human life. There are many methods of Ahara paka mentioned in Ayurveda Shastra. After cooking the quality of food item is transformed to a new improved quality from its original quality and this phenomenon is known as Samskara (food processing). That’s why we can say that Ahara cooking (Soopa Shastra) method is an important art which changes quality of our diet accordingly as desired by us in terms of taste, nutrition, health condition and also according to seasonal variations. Therefore Ahara paka plays an important role in keeping people healthy and helps in treatment of ailing conditions and so Ahara paka method is very essential for day to day life. In this research work we have collected the various classical food items along with ingredients, method of preparation, quality and uses in various health conditions described in Brihatrayee, Laghutrayee and different other classics which will be benefited in different context of uses.